Case studies in financial decision making - Harrington, Diana R. (Dryden Press, 1994)
Contents: Analyzing corporate performance; Forecasting future corporate performance; capital budgeting; required return on investment - cost of capital; financing capital investments; strategic investment and financing decisions; technical note.